Identification of Mucorales isolates from soil using morphological and molecular methods - Ardeshir Ziaee; Mohammadali Zia; Mansour Bayat; Jamal Hashemi (Mazandaran University of Medical Sciences, 2016)
Background and Purpose: Soil is the main habitat of saprophytic and pathogenic fungi. Mucormycetes are one of the most parts of soil fungi and certain members are among opportunistic fungi and can cause systemic fungal infections in immunocompromised patients. The majority of human and animal infections are caused by members of the genera Rhizopus, Mucor, Rhizomucor, Lichtheimia (Absidia), Cunninghamella and Mortierella. The objective of this research was to isolate and identify the main genera of Zygomycetes, using molecular assay and morphological features. Materials and Methods: A total of 340 soil samples were collected from different sites of seven public parks and 14 municipality districts in Isfahan. All samples were cultured on appropriate media and incubated at 27° C for 2 to 4 days, and then examined daily for visible fungal growth. PCR-RFLP method and macroscopic, microscopic and physiological characteristics were applied to identify fungal colonies. Results: Four hundred pure colonies belonging to six genera of Zygomycetes including Lichtheimia, Rhizopus, Rhizomucor, Mucor, Cunninghamella and Mortierella were identified. The genus Rhizopus (35.5%) was the most frequent isolate, followed by Mucor (32.25%) and Rhizomucor (27.5%). Conclusion: These finding may help us to understand about the importance of opportunistic fungi in public areas and the risk of exposure with immunocompromised persons.